Overexpression of the Transcription Factor AtLEC1 Significantly Improved the Lipid Content of Chlorella ellipsoidea - Liu, Xiao; Zhang, Dan; Zhang, Jianhui; Chen, Yuhong; Liu, Xiuli; Fan, Chengming; Wang, Richard R-C.; Hou, Yongyue; Hu, Zanmin (Frontiers in Bioengineering and Biotechnology, 2021)
Microalgae are considered to be a highly promising source for the production of biodiesel. However, the regulatory mechanism governing lipid biosynthesis has not been fully elucidated to date, and the improvement of lipid accumulation in microalgae is essential for the effective production of biodiesel. In this study, LEAFY COTYLEDON1 (LEC1) from Arabidopsis thaliana, a transcription factor (TF) that affects lipid content, was transferred into Chlorella ellipsoidea. Compared with wild-type strains, the total fatty acid content and total lipid content of AtLEC1 transgenic strains were significantly increased by 24.20-32.65% and 22.14-29.91%, respectively, under mixotrophic culture conditions and increased by 24.4-28.87% and 21.69-30.45%, respectively, under autotrophic conditions, while the protein content of the transgenic strains was significantly decreased by 18.23-21.44% and 12.28-18.66%, respectively, under mixotrophic and autotrophic conditions. Fortunately, the lipid and protein content variation did not affect the growth rate and biomass of transgenic strains under the two culture conditions. According to the transcriptomic data, the expression of 924 genes was significantly changed in the transgenic strain (LEC1-1). Of the 924 genes, 360 were upregulated, and 564 were downregulated. Based on qRT-PCR results, the expression profiles of key genes in the lipid synthesis pathway, such as ACCase, GPDH, PDAT1 and DGAT1, were significantly changed. By comparing the differentially expressed genes (DEGs) regulated by AtLEC1 in C. ellipsoidea and Arabidopsis, we observed that approximately 59% (95/160) of the genes related to lipid metabolism were upregulated in AtLEC1 transgenic Chlorella. Our research provides a means of increasing lipid content by introducing exogenous TF and presents a possible mechanism of AtLEC1 regulation of lipid accumulation in C. ellipsoidea.